Implementasi Pemasangan Reklame Berdasarkan Peraturan Walikota Denpasar Nomor 3 Tahun 2014 tentang Penyelenggaraan Reklame - da Bagus Gde Wisnu wardhana; I Ketut Kasta Arya Wijaya; Luh Putu Suryani (Warmadewa Press, 2021)
The implementation of billboards through their installation at this time still does not follow the procedures regulated by the existing legal regulations, resulting in an impression of disorder along roads in Denpasar City which are considered to be damaging to aesthetic and cleanliness values due to poor arrangement. Basically the function of billboards is to convey information, but if there is an irregularity in the installation, the public is reluctant to see the contents of it, so legal rules are needed related to this issue. This method used is empirical research, then the approach is carried out sociologically. Primary data from this research is by conducting interviews with the Denpasar City Civil Service Police Unit (Satpol PP). In addition, the use of Denpasar Mayor Regulation Number 3 of 2014 concerning the Implementation of Advertising. to literature books, related journals also help this research. The result of the research indicates that IMB-R and SIPR can only be issued according to the needs of the advertisement organizer based on the Regulation of the Mayor of Denpasar Number 3 of 2014, in controlling billboards that do not have IMB-R and SIPR permits based on the Regulation of the Mayor of Denpasar Number 3 of 2014 carried out by the Organization. The Regional Government of Denpasar City based on the Decree of the Mayor of Denpasar Number 188.45 / 422 / HK / 2013 concerning the formation of a team for organizing the Denpasar City billboard. Controlling the installation of billboards, namely written warnings to advertisement organizers and demolition of billboards.